Tuberculosis as a Predicator of Childhood Malnutrition in Sindh, Pakistan (Medical Forum Monthly, 2024)
Objective: To assess the prevalence and identify risk factors associated with Mycobacterium tuberculosis infection in Sindh, Pakistan. Study Design: Quantitative and cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Pulmonology, and Department of Biochemistry Ghulam Muhammad Mahar Medical College, Sukkur from January 2016 to May, 2019. Materials and Methods: Diagnosis of TB was performed by AFB smear and X-ray chest. For the screening of malnutrition, blood sample were collected and Total Protein, Albumin and A/G ratio were analyzed. Body Mass Index (BMI) were estimated by analyzing data from questioners. Results: Overall 170 children were recruited in this studu, 81 were male and 89 were female. It was estimated that 13% children were infected eithTuberculosis every each year. Malnutrition was highly prevalent in TB infected children. Conclusion: This seems to be a relationship between malnutrition and an increased risk of TB in children belong to remote areas of Sindh, Pakistan.